T1-T2 Disk Herniation Presenting With Horner Syndrome: A Case Report With Literary Review. (November 2018) - Possley, Daniel; Luczak, S. Brandon; Angus, Andrew; Montgomery, David
Abstract : Horner syndrome or oculosympathetic paresis is caused by interruption of the sympathetic nerve supply to the face and eye that manifests as facial anhidrosis, blepharoptosis, and miosis. This sympathetic pathway begins in the hypothalamus and synapses in the intermediolateral gray substance of the spinal cord at C8-T2 levels making it susceptible to disruption via a high thoracic intervertebral disk herniation. We present a rare case of a patient with T1-T2 intervertebral disk herniation and Horner syndrome who was treated surgically. After confirming the diagnosis with MRI, the patient was treated with standard posterior approach with laminoforaminotomy and diskectomy. Although posterior approach surgery is most commonly used for laminectomy and/or foraminotomy, successful anterior approaches to upper thoracic lesions are valid as well. Our patient had resolution of his back pain, paresthesias, and grip weakness at 6 weeks postoperatively, but his Horner syndrome persisted at latest follow-up. Patients with cervical radiculopathy symptoms and physical examination findings consistent with Horner syndrome should be evaluated with a MRI that includes the upper thoracic spine. An accurate diagnosis and timely surgical intervention may provide the patient the best chance for regression of symptoms and a satisfactory outcome.